2021
DOI: 10.1007/s00248-021-01901-w
|View full text |Cite
|
Sign up to set email alerts
|

Temperature and Precipitation Drive Elevational Patterns of Microbial Beta Diversity in Alpine Grasslands

Abstract: Understanding the mechanisms underlying biodiversity patterns is a central issue in ecology, while how temperature and precipitation jointly control the elevational patterns of microbes is understudied. Here, we studied the effects of temperature, precipitation and their interactions on the alpha and beta diversity of soil archaea and bacteria in alpine grasslands along an elevational gradient of 4,300-5,200 m on the Tibetan Plateau. Alpha diversity was examined on the basis of species richness and evenness, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 83 publications
2
4
0
Order By: Relevance
“…Environmental factors profoundly contribute to shaping the soil microbiome, both spatially and temporally [5]. Precipitation, temperature, and their interaction are considered to be important factors affecting grassland microbial diversity [54], and these results were confirmed in the present research (Fig. 7).…”
Section: Discussionsupporting
confidence: 86%
“…Environmental factors profoundly contribute to shaping the soil microbiome, both spatially and temporally [5]. Precipitation, temperature, and their interaction are considered to be important factors affecting grassland microbial diversity [54], and these results were confirmed in the present research (Fig. 7).…”
Section: Discussionsupporting
confidence: 86%
“…There was a similar nding in other studies (e.g., Liu et al, 2013;Najjar et al, 2020;Jiang et al, 2021). This may be due to the large difference in water temperature between seasons (Yang et al, 2022). The study of Ruhl et al (2022) also indicated that temperature is a major factor limiting the taxonomic and functional diversity of microbial communities.…”
Section: Temporal Variation In Microbial Community and The Driving Fa...supporting
confidence: 82%
“…There was a similar finding in other studies (e.g., Liu et al, 2013 ; El Najjar et al, 2020 ; Jiang et al, 2021 ). This may be due to the large difference in water temperature between seasons (Yang et al, 2022 ). In this study, the RDA result indicated that the temperature was the main driving factor for microbial community composition ( Supplementary Table S2 ), and the mantel's test also proved that the temperature was significantly correlated with bacteria and archaea ( Figure 8 ).…”
Section: Discussionmentioning
confidence: 99%